High-temperature-resistant ceramsite oil well proppant and preparation method thereof
By using ceramic substrates, nano-reinforced materials, intelligent temperature control materials and optimized bonding systems in petroleum mining proppants, the insufficient performance of existing proppants in deep high temperature and high pressure environments is solved, and high strength is achieved. Toughness and high temperature resistance.
Patent Information
- Application Number
- CN202411632223.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-15
AI Technical Summary
The proppants in existing oil mining show low compressive strength, poor temperature resistance, insufficient surfactivity and unreasonable particle size distribution in deep high temperature and high pressure environments, resulting in a decrease in flow diversion capacity and unstable fracturing gaps.
Using ceramic substrates, nano-reinforced materials, intelligent temperature control materials, optimized bonding systems and reinforced fibers, we form a high-strength, high toughness and high temperature resistance proppant through innovative material design and structural ratio.
It realizes the high strength, toughness and flow diversion ability of proppant in high temperature and high pressure environments, and has excellent high temperature resistance and thermal protection effects, ensuring the support effect and reliability of the oil well.
Smart Images

Figure BDA0005136215250000091 
Figure BDA0005136215250000101 
Figure BDA0005136215250000111
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of oil extraction, and in particular to a high temperature resistant ceramsite oil well proppant and a preparation method thereof. Background Art
[0002] In the field of oil and gas development, proppants are key materials for maintaining fracture gaps, and their performance directly determines the fracturing effect and oil and gas recovery rate. As oil and gas exploration and development move toward deep and ultra-deep layers, traditional proppants can no longer meet the stringent requirements under high temperature and high pressure environments. Although existing proppant technology has undergone years of development and improvement, there are still many technical problems that need to be solved.
[0003] At present, the main proppants used in the market include three categories: quartz sand, ceramsite and resin-coated proppants. Among them, quartz sand proppants are widely used in the development of shallow oil and gas reservoirs because of their wide sources and low costs. However, with the increase in exploration depth, its inherent performance defects have become increasingly prominent. The compressive strength of quartz sand proppants is generally lower than 52MPa, and it is very easy to break under deep high-pressure environments, resulting in the closure of support gaps and seriously affecting the flow conductivity. In addition, its temperature resistance is poor, and it will soften and deform when the temperature exceeds 150°C, which cannot meet the development needs of deep high-temperature oil and gas reservoirs.
[0004] Although ceramsite proppants have been improved in strength and temperature resistance, they still have significant shortcomings. Traditional ceramsite proppants are designed with a single component and have single performance, which makes it difficult to adapt to the diverse needs under complex formation conditions. They have poor surface activity and poor compatibility with formation fluids, which affects the support effect. Especially when the formation temperature changes drastically, thermal stress cracking is prone to occur due to the lack of temperature control function. At the same time, the particle size distribution of existing ceramsite proppants is not reasonable enough, making it difficult to form an optimal stacking structure, which affects the stability and conductivity of the support gap.
[0005] In order to improve the surface properties of proppants, the industry has developed resin-coated proppants, but this improvement has not fundamentally solved the technical problems faced by deep oil and gas reservoir development. The resin coating is prone to aging when the temperature exceeds 180°C, resulting in a sharp drop in performance. More seriously, after the resin is cured, it is easy to form an overall "hardening" phenomenon, which seriously affects the conductivity of the fracture. In addition, due to the lack of effective interface control technology, the bonding strength between the resin layer and the proppant body is insufficient, and it is easy to peel off under high temperature and high pressure environment, losing the modification effect. Summary of the invention
[0006] In order to solve or partially solve the problems existing in the related art, the present invention application provides a high-temperature resistant expanded clay oil well proppant, which includes the following components by weight: 60-70 parts of expanded clay base material, 8-12 parts of nano-reinforcement material, 8-12 parts of intelligent temperature control material, 12-18 parts of bonding system and 3-8 parts of reinforcing fiber.
[0007] Furthermore, the ceramsite substrate comprises:
[0008] 45-50 parts of high-purity alumina ceramsite, with a purity of ≥99.5%, and a three-level particle size distribution, of which 1.2-1.5mm accounts for 30%, 0.8-1.2mm accounts for 50%, and 0.5-0.8mm accounts for 20%;
[0009] 15-20 parts of special silicon carbide ceramsite with a purity of ≥98% and 5-8% titanium carbide doped on the surface.
[0010] Furthermore, the nano-enhanced material comprises:
[0011] Silane coupling agent modified nano-alumina 6-8 parts, with a particle size of 20-50nm and a specific surface area of ≥200m 2 / g;
[0012] 2-4 parts of plasma activated nano silicon carbide, with a particle size of 30-70nm and a purity of ≥99%.
[0013] Furthermore, the intelligent temperature control material includes:
[0014] 4-5 parts of low-temperature phase change material, potassium nitrate-based, phase change temperature 334°C;
[0015] 1-2 parts of high temperature phase change material, potassium sulfate based, phase change temperature 1069°C;
[0016] 3-5 parts of shape memory alloy, nickel-titanium based, phase transition temperature 400-500℃.
[0017] Further, the bonding system comprises:
[0018] 8-12 parts of modified PLA main binder, with a molecular weight of 150,000-200,000 and grafted maleic anhydride 2-3wt%;
[0019] 2-4 parts of PCL toughening component, with a molecular weight of 80,000-100,000;
[0020] 2 parts of composite coupling agent.
[0021] Furthermore, the reinforcing fiber comprises:
[0022] 2-4 pieces of surface oxidized carbon fiber, with a length of 3-5mm and a tensile strength of ≥3500MPa;
[0023] 1-4 parts of silanized glass fibers, with a length of 3-4 mm and a diameter of 8-12 μm.
[0024] It is to be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present invention.
[0025] Beneficial technical effects of the present invention:
[0026] The proppant of the present invention achieves significant improvement in mechanical and thermal properties through innovative material design and optimized structural ratio. It not only has high strength, high toughness and excellent compressive resistance, but also exhibits excellent high temperature resistance and thermal protection effects. Its unique intelligent temperature control system gives the material temperature adaptability and shape memory effect, the multiple coupling system ensures the close combination of the components, and the synergistic effect of the multi-level structure optimizes the product performance. The various performance advantages complement each other, thus becoming a new type of support material with comprehensive performance and high reliability. DETAILED DESCRIPTION
[0027] The optional embodiments of the present invention will be described in more detail below. Although the optional embodiments of the present invention are described, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments described herein. On the contrary, these embodiments are provided to make the present invention more thorough and complete, and to fully convey the scope of the present invention to those skilled in the art.
[0028] The terms used in this application are only for the purpose of describing specific embodiments and are not intended to limit this application. The singular forms of "a", "said" and "the" used in this application and the appended claims are also intended to include plural forms unless the context clearly indicates other meanings. It should also be understood that the term "and / or" used herein refers to and includes any or all possible combinations of one or more associated listed items.
[0029] The present invention application provides a high temperature resistant ceramsite oil well proppant, which comprises the following components by weight: 60-70 parts of ceramsite base material, 8-12 parts of nano-reinforcement material, 8-12 parts of intelligent temperature control material, 12-18 parts of bonding system and 3-8 parts of reinforcing fiber.
[0030] The high temperature resistant ceramsite oil well proppant has the following characteristics:
[0031] 1. High strength and high temperature resistance
[0032] High purity alumina (≥99.5%) and silicon carbide (≥98%) ceramsite are used as the base material to provide excellent mechanical strength
[0033] The three-level particle size distribution design (1.2-1.5mm, 0.8-1.2mm, 0.5-0.8mm) ensures the optimal packing density of particles
[0034] Titanium carbide doping (5-8%) on the silicon carbide surface further enhances wear resistance and thermal conductivity
[0035] 2. Nano-enhancement effect
[0036] Nano-alumina is modified by silane coupling agent and has a large specific surface area (≥200m 2 / g), significantly improving the interface bonding strength
[0037] Plasma activated nano-SiC provides additional reinforcement, improving overall performance
[0038] Nano-scale dispersion significantly improves the mechanical properties and thermal stability of the material
[0039] 3. Intelligent temperature control function
[0040] Adopt dual phase change material system:
[0041] Low temperature phase change material (334℃) provides thermal regulation in the medium temperature range
[0042] High temperature phase change material (1069℃) ensures thermal protection under extreme high temperature conditions
[0043] Nickel-titanium-based shape memory alloys provide reversible deformation capabilities in the temperature range of 400-500°C, increasing the material's adaptability
[0044] 4. Optimized bonding system
[0045] Modified PLA main binder has high molecular weight (150,000-200,000), providing good mechanical properties Maleic anhydride graft modification (2-3wt%) improves interfacial compatibility
[0046] PCL toughening components significantly improve toughness and prevent brittle fracture
[0047] Composite coupling agent further strengthens interface bonding
[0048] 5. Fiber synergistic reinforcement
[0049] Surface oxidized carbon fiber has ultra-high tensile strength (≥3500MPa), providing significant reinforcement effect. Silanized glass fiber provides additional reinforcement and improves the toughness of the material.
[0050] The dual fiber system forms a three-dimensional network structure, providing multi-dimensional reinforcement
[0051] In one embodiment of the present invention, the ceramsite substrate comprises:
[0052] 45-50 parts of high-purity alumina ceramsite, with a purity of ≥99.5%, and a three-level particle size distribution, of which 1.2-1.5mm accounts for 30%, 0.8-1.2mm accounts for 50%, and 0.5-0.8mm accounts for 20%;
[0053] 15-20 parts of special silicon carbide ceramsite with a purity of ≥98% and 5-8% titanium carbide doped on the surface.
[0054] In one embodiment of the present invention, the nano-enhanced material comprises:
[0055] Silane coupling agent modified nano-alumina 6-8 parts, with a particle size of 20-50nm and a specific surface area of ≥200m 2 / g;
[0056] 2-4 parts of plasma activated nano silicon carbide, with a particle size of 30-70nm and a purity of ≥99%.
[0057] In one embodiment of the present invention, the intelligent temperature control material includes:
[0058] 4-5 parts of low-temperature phase change material, potassium nitrate-based, phase change temperature 334°C;
[0059] 1-2 parts of high temperature phase change material, potassium sulfate based, phase change temperature 1069°C;
[0060] 3-5 parts of shape memory alloy, nickel-titanium based, phase transition temperature 400-500℃.
[0061] In one embodiment of the present application, the bonding system comprises:
[0062] 8-12 parts of modified PLA main binder, with a molecular weight of 150,000-200,000 and grafted maleic anhydride 2-3wt%;
[0063] 2-4 parts of PCL toughening component, with a molecular weight of 80,000-100,000;
[0064] 2 parts of composite coupling agent.
[0065] In one embodiment of the present invention, the reinforcing fiber comprises:
[0066] 2-4 pieces of surface oxidized carbon fiber, with a length of 3-5mm and a tensile strength of ≥3500MPa;
[0067] 1-4 parts of silanized glass fibers, with a length of 3-4 mm and a diameter of 8-12 μm.
[0068] For the purpose of greater clarity, the invention is described in detail through the following examples.
[0069] Embodiment 1:
[0070] By weight, it includes the following components:
[0071] 1. 60 parts of ceramsite substrate:
[0072] - 45 parts of high-purity alumina ceramsite (purity 99.5%, 1.2-1.5mm accounts for 30%, 0.8-1.2mm accounts for 50%, 0.5-0.8mm accounts for 20%)
[0073] - 15 parts of special silicon carbide ceramsite (98% purity, 5% titanium carbide doped on the surface)
[0074] 2. 8 parts of nano-enhanced materials:
[0075] - 6 parts of silane coupling agent modified nano-alumina (particle size 20nm, specific surface area 200m 2 / g)-2 parts of plasma activated nano silicon carbide (particle size 30nm, purity 99%)
[0076] 3. 8 pieces of intelligent temperature control materials:
[0077] - 4 parts of low-temperature phase change material (potassium nitrate based, phase change temperature 334°C)
[0078] -1 part of high temperature phase change material (potassium sulfate based, phase change temperature 1069°C)
[0079] -3 parts of shape memory alloy (nickel-titanium based, phase transition temperature 400°C)
[0080] 4. Adhesive system 12 parts:
[0081] - Modified PLA main binder 8 parts (molecular weight 150,000, grafted maleic anhydride 2wt%)
[0082] -2 parts of PCL toughening component (molecular weight 80,000)
[0083] - 2 parts of composite coupling agent
[0084] 5. 3 parts of reinforcing fiber:
[0085] - 2 pieces of surface oxidized carbon fiber (length 3mm, tensile strength 3500MPa)
[0086] -1 part of silanized glass fiber (length 3mm, diameter 8μm)
[0087] Embodiment 2:
[0088] By weight, it includes the following components:
[0089] 1. 65 parts of ceramsite substrate:
[0090] - 47.5 parts of high-purity alumina ceramsite (purity 99.5%, 30% of 1.2-1.5mm, 50% of 0.8-1.2mm, 20% of 0.5-0.8mm)
[0091] - 17.5 parts of special silicon carbide ceramsite (98% purity, 6.5% titanium carbide doped on the surface)
[0092] 2. 10 parts of nano-enhanced materials:
[0093] - 7 parts of silane coupling agent modified nano-alumina (particle size 35nm, specific surface area 200m 2 / g)-plasma activated nano silicon carbide 3 parts (particle size 50nm, purity 99%)
[0094] 3. 10 pieces of intelligent temperature control materials:
[0095] - 4.5 parts of low-temperature phase change material (potassium nitrate-based, phase change temperature 334°C)
[0096] -1.5 parts of high temperature phase change material (potassium sulfate based, phase change temperature 1069°C)
[0097] - 4 parts of shape memory alloy (nickel-titanium based, phase transition temperature 450°C)
[0098] 4. Adhesive system 15 parts:
[0099] - Modified PLA main binder 10 parts (molecular weight 175,000, grafted maleic anhydride 2.5wt%) - PCL toughening component 3 parts (molecular weight 90,000)
[0100] - 2 parts of composite coupling agent
[0101] 5.5 parts of reinforcing fiber:
[0102] - 3 pieces of surface oxidized carbon fiber (length 4mm, tensile strength 3500MPa)
[0103] - 2.5 parts of silanized glass fiber (length 3.5 mm, diameter 10 μm)
[0104] Embodiment 3:
[0105] By weight, it includes the following components:
[0106] 1. 70 parts of ceramsite substrate:
[0107] - 50 parts of high-purity alumina ceramsite (purity 99.5%, 1.2-1.5mm accounts for 30%, 0.8-1.2mm accounts for 50%, 0.5-0.8mm accounts for 20%)
[0108] - 20 parts of special silicon carbide ceramsite (98% purity, 8% titanium carbide doped on the surface)
[0109] 2. 12 parts of nano-enhanced materials:
[0110] - 8 parts of silane coupling agent modified nano-alumina (particle size 50nm, specific surface area 200m 2 / g)-4 parts of plasma activated nano silicon carbide (particle size 70nm, purity 99%)
[0111] 3. 12 pieces of intelligent temperature control materials:
[0112] - 5 parts of low-temperature phase change material (potassium nitrate based, phase change temperature 334°C)
[0113] -2 parts of high temperature phase change material (potassium sulfate based, phase change temperature 1069°C)
[0114] -5 parts of shape memory alloy (nickel-titanium based, phase transition temperature 500°C)
[0115] 4. Adhesive system 18 parts:
[0116] - Modified PLA main binder 12 parts (molecular weight 200,000, grafted maleic anhydride 3wt%)
[0117] - 4 parts of PCL toughening component (molecular weight 100,000)
[0118] - 2 parts of composite coupling agent
[0119] 5. Reinforcement fiber 8 parts:
[0120] - 4 pieces of surface oxidized carbon fiber (length 5mm, tensile strength 3500MPa)
[0121] - 4 parts of silanized glass fiber (length 4mm, diameter 12μm)
[0122] Test Example 1. High temperature stability test
[0123] Purpose: To verify the physical and chemical stability of proppants in extreme high temperature environments and ensure their reliability in high temperature conditions of oil wells.
[0124] Experimental steps:
[0125] Sample preparation:
[0126] Product of the present invention: Take 3 groups of proppant samples of Example 2, each group is 50 grams.
[0127] Commercially available products (control group): 3 groups of common commercially available expanded clay proppant samples were taken, 50 grams per group.
[0128] Thermogravimetric analysis (TGA):
[0129] Under nitrogen protection, the sample was gradually heated from room temperature to 1200°C, and the mass changes at different temperatures were recorded to determine the heat resistance limit.
[0130] High temperature immersion test:
[0131] The samples were placed in a high temperature furnace at 334°C, 500°C, 800°C and 1069°C and heated for 24 hours.
[0132] After heating, the samples were taken out, the mass loss was recorded, and their morphological changes and structural integrity were observed.
[0133] X-ray diffraction (XRD) analysis:
[0134] XRD analysis was performed on the samples after high temperature treatment to detect the crystal phase changes and evaluate the chemical stability.
[0135] Experimental data:
[0136]
[0137] Result analysis:
[0138] TGA mass loss rate: At all temperatures, the mass loss rate of the product of the present invention is lower than that of the commercially available product, especially at high temperatures (800°C and 1069°C), the difference is significant.
[0139] Mass loss after immersion: The product of the present invention has less mass loss after high temperature immersion, indicating its better high temperature stability.
[0140] Crystal phase change: The crystal phase change of the product of the present invention under high temperature treatment is milder than that of commercially available products, maintaining better structural integrity.
[0141] Test Example 2. Mechanical Strength Test
[0142] Purpose: To evaluate the compressive and tensile strength of proppants at high temperatures to ensure their load-bearing capacity and stability in oil wells.
[0143] Experimental steps:
[0144] Sample preparation:
[0145] The product of the present invention: the proppant sample of Example 2 was treated at room temperature and 800° C. respectively.
[0146] Commercially available products (control group): Commercially available ceramsite proppant samples of the same standard size were prepared and treated at room temperature and 800°C, respectively.
[0147] Compressive strength test:
[0148] Use a universal material testing machine to test the compressive strength of the samples before and after treatment, and record the maximum bearing capacity.
[0149] Tensile strength test:
[0150] The tensile strength of the reinforcing fiber was measured at room temperature and 800°C using a tensile testing machine.
[0151] Data recording and analysis:
[0152] Compare the compressive and tensile strengths at different temperatures to evaluate the high temperature mechanical properties of the material.
[0153] Experimental data:
[0154]
[0155] Result analysis:
[0156] Compressive strength: at 800°C, the compressive strength of the product of the present invention drops from 150MPa to 135MPa, a decrease of only 10%; while the commercially available product drops from 130MPa to 110MPa, a decrease of about 15.4%, indicating that the product of the present invention has better high-temperature bearing capacity.
[0157] Tensile strength: At 800°C, the tensile strength of the product of the present invention drops from 3600MPa to 3300MPa, a decrease of about 8.3%; the commercially available product drops from 3200MPa to 2800MPa, a decrease of about 12.5%, indicating that the product of the present invention maintains a higher tensile strength at high temperatures.
[0158] Test Example 3. Thermal Control Performance Test
[0159] Purpose: To verify the role of intelligent temperature control materials in proppants, evaluate their phase change temperature and heat absorption / release capabilities, and ensure effective temperature regulation in oil wells.
[0160] Experimental steps:
[0161] Sample preparation:
[0162] The product of the present invention: 3 groups of proppant samples containing intelligent temperature control materials in Example 2.
[0163] Commercially available products (control group): 3 groups of commercially available expanded clay proppant samples without intelligent temperature control materials were taken.
[0164] Differential Scanning Calorimetry (DSC):
[0165] Determine the phase change temperature and latent heat of low-temperature phase change materials (potassium nitrate based), high-temperature phase change materials (potassium sulfate based) and shape memory alloys (nickel-titanium based).
[0166] Thermal Cycle Test:
[0167] The sample was subjected to 10 thermal cycles (heating to the phase transition temperature and then cooling) to observe the stability of its heat absorption / release ability.
[0168] Data recording and analysis:
[0169] The phase change temperature and latent heat change of each thermal cycle are recorded to evaluate the repeatability and reliability of the intelligent temperature control material.
[0170] Experimental data:
[0171]
[0172]
[0173] Result analysis:
[0174] Phase change temperature and latent heat: After 10 thermal cycles, the phase change temperature and latent heat of the intelligent temperature control material in the product of the present invention remain almost unchanged (the change does not exceed 1°C and 1J / g), showing excellent thermal control performance and repeatability; while the commercially available products cannot achieve the temperature regulation function because they do not contain intelligent temperature control materials.
[0175] Thermal management capability: The product of the present invention can effectively absorb or release heat at different temperature stages to maintain the temperature of the oil well environment stable, while commercially available products lack this function and cannot adjust the temperature.
[0176] Summarize
[0177] Through three key experiments, namely high temperature stability test, mechanical strength test and thermal control performance test, the data show that:
[0178] High temperature stability:
[0179] The mass loss rate of the product of the present invention at all test temperatures is lower than that of commercially available products, and especially at high temperatures (800° C. and 1069° C.), it exhibits more excellent stability.
[0180] The crystal phase change is milder than that of commercially available products, maintaining better structural integrity.
[0181] Mechanical strength:
[0182] The compressive and tensile strengths of the product of the present invention in a high temperature environment are higher than those of commercially available products, showing stronger bearing capacity and stability.
[0183] Thermal control performance:
[0184] The product of the present invention realizes effective temperature regulation and thermal management capabilities by containing intelligent temperature control materials, while commercially available products cannot achieve this function.
[0185] Although the present invention has been described in detail above with general descriptions and specific embodiments, it is obvious to those skilled in the art that some modifications or improvements may be made based on the present invention. Therefore, these modifications and improvements made without departing from the spirit of the present invention all fall within the scope of protection claimed by the present invention.
Claims
1. A high temperature resistant ceramsite oil well proppant, characterized in that: The invention comprises the following components by weight: 60-70 parts of ceramsite base material, 8-12 parts of nano-reinforcement material, 8-12 parts of intelligent temperature control material, 12-18 parts of bonding system and 3-8 parts of reinforcing fiber.
2. The high temperature resistant ceramsite oil well proppant according to claim 1, characterized in that: The ceramsite substrate comprises: 45-50 parts of high-purity alumina ceramsite, with a purity of ≥99.5%, and a three-level particle size distribution, of which 1.2-1.5mm accounts for 30%, 0.8-1.2mm accounts for 50%, and 0.5-0.8mm accounts for 20%; 15-20 parts of special silicon carbide ceramsite with a purity of ≥98% and 5-8% titanium carbide doped on the surface.
3. The high temperature resistant ceramsite oil well proppant according to claim 1, characterized in that: The nano-enhanced material comprises: Silane coupling agent modified nano-alumina 6-8 parts, with a particle size of 20-50nm and a specific surface area of ≥200m 2 / g; 2-4 parts of plasma activated nano silicon carbide, with a particle size of 30-70nm and a purity of ≥99%.
4. The high temperature resistant ceramsite oil well proppant according to claim 1, characterized in that: The intelligent temperature control material comprises: 4-5 parts of low-temperature phase change material, potassium nitrate-based, phase change temperature 334°C; 1-2 parts of high temperature phase change material, potassium sulfate based, phase change temperature 1069°C; 3-5 parts of shape memory alloy, nickel-titanium based, phase transition temperature 400-500℃.
5. The high temperature resistant ceramsite oil well proppant according to claim 1, characterized in that: The bonding system comprises: 8-12 parts of modified PLA main binder, with a molecular weight of 150,000-200,000 and grafted maleic anhydride 2-3wt%; 2-4 parts of PCL toughening component, with a molecular weight of 80,000-100,000; 2 parts of composite coupling agent.
6. The high temperature resistant ceramsite oil well proppant according to claim 1, characterized in that: The reinforcing fibers include: 2-4 pieces of surface oxidized carbon fiber, with a length of 3-5mm and a tensile strength of ≥3500MPa; 1-4 parts of silanized glass fiber, with a length of 3-4 mm and a diameter of 8-12 μm.
Citation Information
Patent Citations
Hydraulic fracturing method for stratum
CN101371005A
Low-density and high-strength silicon-carbide-based fracturing proppant
CN102220125A
Proppant and application thereof
CN111876143A
Modified silicon carbide type ceramsite proppant and matched fracturing fluid system and use method thereof
CN113201323A